Proposed independent organisational structure for memory institutions in Zimbabwe and South Africa. (24th August 2021) - Bhebhe, Sindiso
Abstract : Purpose: The idea of convergence of cultural institutions, especially the libraries, archives and museums (LAMS) to operate as one, has a long theoretical history which unfortunately has not been translated into practice. This subject has been discussed by a number of scholars but the implementation has just remained theoretical with only a few countries practically adopting such an organisational structure. In Africa, this concept of LAMS is yet to gain traction. Therefore, the purpose of this paper is aimed at proposing such LAMS structures for African nations, especially in Zimbabwe and South Africa considering the emergence of community "archives" which have blurred further the distinction between museology, archiving and librarianship. The motivation in advocating for the adoption of LAMS is also driven by the theory behind participatory archives which thrive on the advanced use of internet including social media platforms that can make it possible to have one-stop virtual archive on the cloud that also incorporates museums and libraries. Design/methodology/approach: This is a concept paper which reviewed the literature on national and community archives in Zimbabwe and South Africa which were purposively selected because of their long history in archiving. This was done to come up with a proposed "independent" national heritage organisational structure. "Independent" structure because this paper was based on the assumption that the independence of decision-making in national archival structures in Zimbabwe and South Africa is compromised and biased towards the ethos of political parties' ruling governments. Findings: Proposed integrated framework for community archives into the sustainable national archival system which also incorporates the role that can be played by universities. The framework is likely to be feasible and of benefit in the countries that are struggling to have national mainstream independent archives which are just not paying allegiance to those who are in power. Originality/value: This study is unique in the sense that it mixes LAMS and the concept of independent archival structure in a regional comparative nature that involves Zimbabwe and South Africa.